Theoretical and experimental studies on the oil-based emulsion spray - Gong, Chen; Chen, Fujun; Kang, Can (Frontiers in Plant Science, 2023)
Oil-based emulsion is a common herbicide formulation in agricultural spray, and its atomization mechanism is different from water spray. In this paper, a theoretical model based on the characteristics of spray sheet was proposed to predict the spray droplet size for oil-based emulsion spray. An image processing method was used to measure droplet size distributions for different spray pressures and nozzle configurations, and the measured results were used to validate the theoretical model. The results show that oil-based emulsion spray is characterized by the web structure constituted by perforations. The liquid that originally occupied by spray sheet eventually gather in these web structures. The proposed theoretical model is based on the size of nozzle exit, angle of spray sheet and perforation number in the web structure, which are relatively easy to obtain. The theoretical droplet size is in inverse proportion to the square root of perforation number in web structure, while in proportion to the square root of the area of nozzle exit. The captured images of spray sheets and the measured droplet size distribution show consistency with the theoretical prediction. The difference between theoretical results and measured volumetric median diameter is less than 10% for different spray pressures and nozzles.